EMERGENCE OF IDEAS OF GENDER EQUALITY IN UZBEK LITERATURE (TAMADDUN NURI JURNALI, 2025)
this article explores the evolution of gender inequality and feminist discourse in Uzbek literature, focusing on the portrayal of women in the early twentieth century. It examines the influence of the Jadids, who advocated for women’s rights, and how their ideas are reflected in the works of writers like Cholpon and Qodiriy.